2019
DOI: 10.3390/mi10120817
|View full text |Cite
|
Sign up to set email alerts
|

Sheathless Shape-Based Separation of Candida Albicans Using a Viscoelastic Non-Newtonian Fluid

Abstract: Rapid and accurate identification of Candida albicans from among other candida species is critical for cost-effective treatment and antifungal drug assays. Shape is a critical biomarker indicating cell type, cell cycle, and environmental conditions; however, most microfluidic techniques have been focused only on size-based particle/cell manipulation. This study demonstrates a sheathless shape-based separation of particles/cells using a viscoelastic non-Newtonian fluid. The size of C. albicans was measured at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Li et al 38 demonstrated the ability of viscoelastic microfluidics to separate normal and multimetric drug-treated human fungal pathogen Cryptococcus neoformans by morphol-ogy. Nam et al 39 utilized a viscoelastic fluid for shape-based separation of pathogenic yeast Candida albicans of relatively large size (i.e., up to 32 μm in length). However, it has not been shown whether elasto-inertial effects can be used to separate S. Cerevisiae, an important industrial workhorse and a model organism, based on shape.…”
mentioning
confidence: 99%
“…Li et al 38 demonstrated the ability of viscoelastic microfluidics to separate normal and multimetric drug-treated human fungal pathogen Cryptococcus neoformans by morphol-ogy. Nam et al 39 utilized a viscoelastic fluid for shape-based separation of pathogenic yeast Candida albicans of relatively large size (i.e., up to 32 μm in length). However, it has not been shown whether elasto-inertial effects can be used to separate S. Cerevisiae, an important industrial workhorse and a model organism, based on shape.…”
mentioning
confidence: 99%
“…RNA, or particles. In the latter case, many studies have addressed the physics of particle focusing in Poiseuille flows 40,41 , and recent interest has emerged for microorganism separation 42 , but dispersion remains to be studied and modelled, potentially with the same types of arguments based on the Taylor model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Lu et al [ 25 , 26 ] experimentally found that particles can be sorted by their shape/morphology in viscoelastic microfluidics [ 27 , 28 , 29 ]. Later, based on the simple shape-dependent migration principle, viscoelastic fluids were adopted to separate abnormal-shaped yeast cells from those that were regular shaped [ 30 ], incubated Candida albicans with germ tube formations from spherical candida cells [ 31 ], and cyanobacterial Anabaena with different rod aspect ratios [ 32 ]. Moreover, Yang et al [ 33 ] demonstrated that elasto-inertial particles can also be sorted by their deformability, successfully isolating rigidified RBCs from fresh RBCs.…”
Section: Introductionmentioning
confidence: 99%